Cloud Atlas : A Novel - Mitchell, David (David Stephen) (London Sceptre, 2004)
The narrators of Cloud Atlas hear each other's echoes down the corridor of history and their destinies are changed in ways great and small. Disparate characters connect, their fates intertwine, and their souls drift through time like clouds across the sky.
Keywords: Reincarnation -- Fate and fatalism -- Voyages, Imaginary